Rola orientacji temporalnej na teraźniejszość w wyjaśnianiu preferowanej strategii seksualnej - Zdybek, Przemysław (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
This paper presents two researches conducted to verify the hypothesis that present temporal orientation is significant variable in describing human preferences of sexual strategies. First survey was conducted using as a independent variable two scales measuring temporal orientation: Carpe Diem (Sobol & Oleś, 2002), AION (Bajcar & Nosal, 2004), as a dependent variable was taken preferred sexual strategies measured by Sociosexsual Orientation Inventory (Simpson & Gangestad, 1991). Comparing participants with high rate of present temporal orientation vs low rate of present temporal orientation shows statistically significant differences in Sociosexuality Orientation Scale. Second research confirm hypothesis that participants declaring being sexoholic have higher rate of temporal concentration on presence measured by ZPTI (Zimbardo & Boyd, 2009).